There is No Videogame: Nishida, Posthumanism, and the Basho of Gameplay - Andiloro, Andrea (Journal of Posthumanism, 2024)
This article traverses from humanist to posthumanist philosophies to analyse videogame ontology. It challenges Cartesian dualism, understood as emblematic of humanist thinking, by bringing the philosophy of Nishida Kitarō in conversation with posthumanist thought. Nishida’s rejection of the subject-object split and his concepts of ‘pure experience’, ‘basho’ and ‘action-intuition’ provide a framework for understanding games as dynamic events in a relational matrix of nothingness rather than as discrete entities. The game Jetpack Joyride is analyzed through this lens, illustrating how gameplay is a co-creative experience within a complex interplay of technology and human agency. This approach promotes an inclusive and global understanding of the interconnected nature of videogames and player identities, challenging entrenched Western paradigms in game studies and posthumanist thought.